1997
DOI: 10.1046/j.1365-2168.1997.02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit of colorectal cancer surgery by non-specialist surgeons

Abstract: Background Some authorities recommend that colorectal cancer should be treated in specialist units but evidence that non-specialist units demonstrate comparatively poor results may be lacking. Methods Between 1987 and 1991,267 patients were operated on by four general surgeons, none of whom was a specialist in colorectal surgery. Procedure-related complications, postoperative mortality and disease-related survival rates were analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
3
15
0
1
Order By: Relevance
“…Neoadjuvant radiotherapy was used from single institutions [1,[13][14][15][16][17][18][19][20][21][22][23] or are populationbased outcome studies [24][25][26][27][28][29][30]. Only a minority of studies are nationwide multi-institutional surveys [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…Neoadjuvant radiotherapy was used from single institutions [1,[13][14][15][16][17][18][19][20][21][22][23] or are populationbased outcome studies [24][25][26][27][28][29][30]. Only a minority of studies are nationwide multi-institutional surveys [31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…The recommendations originated from data suggesting that high workload (Schrag et al, 2002) or specialist (Birbeck et al, 2002;McArdle and Hole, 2002;Smith et al, 2003) doctors offered better outcomes than their low workload or generalist counterparts. Unfortunately, however, the evidence available to substantiate this theory is not conclusive (Kee et al, 1999;Parry et al, 1999) and, as a consequence, not all within the health service subscribe to the idea (Singh et al, 1997).…”
mentioning
confidence: 99%
“…Experience and broader education may also be factors influencing the results in rectal cancer treatment. This view is supported by a study reporting that board‐certified colorectal surgeons have a lower in‐hospital mortality rate than other Institutional surgeons [ 22, 23]. In our opinion, specialization in rectal cancer treatment promotes quality not only by increased knowledge and skill in surgical technique but also for other reasons, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the role of both the surgeon and the hospital for the outcome of colorectal cancer treatment has been much debated [ 16–24]. Several studies have shown that the individual surgeon is a prognostic factor for the results, but it seems that skill is more important than case volume [ 18, 19, 23].…”
Section: Introductionmentioning
confidence: 99%